Census of State Adult Correctional Facilities, 1984 ([Verlag nicht ermittelbar], 1987)
This study provides a descriptive analysis of confinement facilities and state-operated community-based correctional facilities nationwide. Decision-makers, practitioners, and researchers may use the census to analyze the current conditions and needs of state correctional facilities for adults. Variables of interest include physical security, age of facilities, functions of facilities, programs, inmate work assignments, staff employment, facilities under court order/consent decree for conditions of confinement, capital and operating expenditures, custody level of residents/inmates, one-day and average daily population counts, race/ethnicity of inmates, inmate work assignments, inmate deaths, special inmate counts, and assaults and incidents by inmates. The institution is the unit of analysis.